2019
DOI: 10.2174/1381612825666190313115233
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Aspects of Longevity: Results from a Sicilian Survey and Implication for the Prevention and Treatment of Age-related Diseases

Abstract: Background: It is well known that long living individuals are a model of successful ageing and that the identification of both genetic variants and environmental factors that predispose to a long and healthy life is of tremendous interest for translational medicine. Methods: We present the preliminary findings obtained from an ongoing study on longevity conducted on a sample of Sicilian long-lived individuals. Results: We review the characteristics of longevity in Sicily, taking into account lifestyle, env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…About the other aspects of lifestyle of these Sicilian LLIs, Accardi et al, have reported that longevity mostly concerns people living in small villages, without pollution, likely because of different working conditions, different lifestyles, i.e ., reduced smoking and alcohol abuse and an anti-inflammatory diet [ 46 ]. Longevity is observed particularly in small municipalities because individuals with greater access to social support and family networks have better health care and lower levels of mortality, particularly when adult daughters are present.…”
Section: Discussionmentioning
confidence: 99%
“…About the other aspects of lifestyle of these Sicilian LLIs, Accardi et al, have reported that longevity mostly concerns people living in small villages, without pollution, likely because of different working conditions, different lifestyles, i.e ., reduced smoking and alcohol abuse and an anti-inflammatory diet [ 46 ]. Longevity is observed particularly in small municipalities because individuals with greater access to social support and family networks have better health care and lower levels of mortality, particularly when adult daughters are present.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on Long Living Individuals (LLIs), i.e . , people > 90 years, allowed to identify specific genes and genotypes involved in pathways thought to influence human lifespan, pathways related to diet, immune-inflammatory responses including stress responses and DNA repair [ 5 , 6 ]. Therefore, genetic variation in bitter taste receptor could directly affect successful ageing by modulating food preference during life [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as it is believed that Apolipoprotein E(ApoE) alleles, which strongly influence longevity in most populations [ 5 , 6 ], might interact with other genes to influence successful aging and longevity [ 13 ], we have analysed the association of TAS2R38 with longevity in conjunction with the Translocase of outer mitochondrial membrane 40 homolog (TOMM40), in linkage disequilibrium with APOE [ 14 ]. The TOMM40 rs2075650 SNP was analysed, since it showed evidence of association with the longevity phenotype [ 14 ], and it is correlated with rs429358, one of the SNPs defining the APOE-ε4 allele together with rs7412 (rs2075650:rs429358 r 2 = 0.56/ D ' = 0.81, rs2075650:rs7412 r 2 = 0.01/ D ' = 0.84) in non-Finnish European populations [ 15 ], both absent among the SNPs on the used chip [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…There were no variety of dishes but rather a monotonous diet, often based on legumes as main choice. 14,19 This dietary habit might influence the ability of an individual to reach extreme longevity by epigenetic modifications. 20 The analysis of body composition demonstrated hyperhydration in extracellular compartment (Diega Cammalleri [DC] + 25%, Filippa Cammalleri [FC] + 21.8%) and lower PhA (PhA mean = 4.6°, DC -2.3°, FC -2°).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning FOXO3A gene, only Filippa carried one copy of the allele associated with longevity (the G SNP). 14 Regarding ApoE, both Diega and Filippa carried e3/e3. The RTL of these two sisters fitted in the range of 60-69 Sicilian women (unpublished observations).…”
Section: Molecular Findingsmentioning
confidence: 99%